STATUS KEWARISAN ANAK YANG LAHIR DARI HASIL SEWA RAHIM MENURUT HUKUM PERDATA DAN KHI - Mairati; Surya Pratama (Al Qadhi, 2023)
The purpose of this research is to analyze and understand the phenomenon of surrogacy from the point of view of applicable law in Indonesia, especially according to the compilation of civil law and Islamic law. This type of research is normative, based on a statutory law approach and a qualitative descriptive approach using content analysis of primary, secondary, and tertiary legal sources. The results of the study were obtained by analyzing diverse and complex legal opinions in the perspective of civil law and the compilation of Islamic law. The amount is more than 1/3 of the legal inheritance, but according to KHI, she can only inherit from her mother's lineage.